Key Issues in Trade Facilitation Summary of World Bank/EU Workshops in Dhaka and Shanghai in 2004 - Roy, Jayanta; Bagai, Shweta (World Bank, Washington, DC, 2012)
Trade facilitation is the ability of countries to deliver goods and services on time at the lowest possible cost. It has emerged as an important issue in unilateral, bilateral, and multilateral trade liberalization. Most countries have embarked on heroic reforms aimed at reducing transaction costs of trade. Thus, among the four new Singapore issues, there was least resistance from World Trade Organization (WTO) member countries to include trade facilitation in the Doha Round discussions. However, all countries are not equally placed in initiating reforms in the complex areas of customs procedures, transport and port logistics, harmonization of standards, and simplification of procedures. Trade facilitation reforms require a large volume of technical assistance for national capacity building. To facilitate what these reforms entail and what can be learned from cross-country experiences, the EU and the World Bank organized two workshops in Dhaka (South Asian countries) and Shanghai (East Asian countries) in 2004. Jointly they succeeded in bringing together renowned experts from multilateral organizations, selected bilateral donor community, the private sector, ex civil servants, and scholars. The participants were largely drawn from the relevant government departments and chambers of commerce and industry. This paper summarizes the main presentations in the workshops. It also indicates the areas that need more focus in future events. The paper should serve as a reference document for national policymakers and for future seminars and workshops on trade facilitation. It has also linked the presentations to the ongoing research work on trade facilitation.